2016
DOI: 10.1515/jas-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Floral Diversity of Pollen Collected by Honey Bees (Apis mellifera L.) – Validation of the Chromatic Assessment Method

Abstract: A b s t r a c t Pollen collected from flowers by forager bees is the only natural protein source for the hive. This nutritional compound is fundamental for the nurse bee and brood development, and for the queen activity. Pollen has a strong influence on colony health. It is also known that the pollen quality, in terms of the amino acid profile and total protein content, varies significantly according to the floral origin. For this reason, the palynological diversity assessed in corbicular pollen is a good meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
(23 reference statements)
3
17
0
Order By: Relevance
“…These findings are again comparable to other studies on pollen diversity 21,26,32 . Compared to the study in Thessaloniki, Greece 15 , we identified more pollen types, which can be attributed to the larger number of rare pollen types in Austria (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are again comparable to other studies on pollen diversity 21,26,32 . Compared to the study in Thessaloniki, Greece 15 , we identified more pollen types, which can be attributed to the larger number of rare pollen types in Austria (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In some countries citizen scientists were also equipped with sample bags and instructions on how to prepare and conserve samples for later palynological analysis in a laboratory. Therefore, comparable results to this Austrian study are available from seven locations in Liguria, Italy 32,34 .…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Pollen-load colours can be used to record the diversity of plants from which bees forage (Kirk, 2006), but caution is needed because one plant species can produce more than one pollen colour and very different species can have pollen loads with identical colours (Hodges, 1952;Hidalgo & Bootello, 1990;Kirk, 2006). However, measurements have shown that there is a good correlation between colour analysis and palynological analysis (Conti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%